Study of resonances in exotic neutron-rich 14Be by the use of isospectral potential. Issue 1 (1st September 2022) - Hasan, M; Alam, M; Mondal, S H; Khan, Md A
Abstract : In this work, Hyperspherical Harmonic Expansion (HHE) formalism aided by supersymmetric quantum mechanics is used to study bound and resonant states of 14 Be in the three-body ( 12 Be+ n + n) cluster model, and the analysis of the resonant states close to the binding threshold utilizes supersymmetric quantum mechanics (SSQM). GPT nucleon-nucleon potential together with SBB core-nucleon potential is chosen for the solution of three-body Schrödinger equation to get the lowest bound state energy and wave function. In the next stage, energy and wave function of the bound state is used to derive an isospectral potential that exhibit deep well following a strong barrier facilitating confinement (or trapping) of particle inside it at some positive energy (E>0). The trapping probability when plotted against energy shows a prominent peak at the energy of resonance. WKB approximation is used to determine the width of resonance width. Calculated resonance energy and width of resonance are compared with those measured experimentally for the promising neutron halo candidate, the 14 Be.